The electoral cycle of international migration flows from Latin America - Brenes Camacho, Gilbert (2010)
There is abundant scientific literature about the effect that politics in destination countries have on immigration flows (Tienda, 2002), as well as about the effect of political and humanitarian crises (wars, famines, etc.) on the probability of migrating (Castles and Miller, 1993). However, there is little research that links emigration flows with elections and other democratic political events at the origin. One of the few studies that provide numerical evidence on how immigration flows vary by election years in the country of origin suggests that, in Nicaragua, either emigration flows towards Costa Rica diminish, or return migration increases, or both. According to a study based on good quality vital statistics in Costa Rica, the typically sharp increase in births by Nicaraguan migrant mothers is stopped or even reversed during the year before elections in Nicaragua and during the electoral year (Brenes-Camacho, 1999). How can elections have an impact on the decision to migrate to another country? Can democratic electoral processes in countries of origin have such an appeal for migrants as to motivate them or discourage them to return home? Given the democratization processes experienced by Latin American countries during the 1980s and 1990s, studying such patterns is important because they might mean that uncontrolled migration flows can be managed or redirected faster than expected by promoting democratic activities and by helping governments from developing countries to fulfill the expectations of their electorates. This article intends to show how political cycles are important in describing temporal patterns in emigration and return migration flows among Latin American migrants. Its goal is to explore the interrelationship between electoral variables and migrants’ economic expectations.